Participation in environmental health research by placenta donation - a perception study - Knudsen Lisbeth E; Mose Tina; Lind Uffe (BMC, 2007)
Abstract Background Much environmental health research depends on human volunteers participating with biological samples. The perception study explores why and how people participate in a placenta perfusion study in Copenhagen. The participation implies donation of the placenta after birth and some background information but no follow up. Methods Nineteen semi-structured qualitative interviews were conducted with participants in the placenta perfusion study after donation of placenta. Observation studies were made of recruitment sessions. Results The interviewed participants are generally in favour of medical research. They participated in the placenta perfusion study due to a belief that societal progress follows medical research. They also felt that participating was a way of giving something back to the Danish health care system. The participants have trust in medical science and scientists, but trust is something which needs to be created through "trust-work". Face-to-face interaction, written information material and informed consent forms play important parts in creating trusting relationships in medical research. Conclusion Medical research ethics do not only amount to specific types of written information material but should also be seen as a number of trust making performances involving researchers as well as research participants.